Beneficial Effects of In Vitro Reconstructed Human Gut Microbiota by Ginseng Extract Fermentation on Intestinal Cell Lines - Margherita Finazzi; Federica Bovio; Matilde Forcella; Marina Lasagni; Paola Fusi; Patrizia Di Gennaro (Microorganisms)
Oxidative stress caused by reactive oxygen species (ROS) affects the aging process and increases the likelihood of several diseases. A new frontier in its prevention includes bioactive foods and natural extracts that can be introduced by the diet in combination with specific probiotics. Among the natural compounds that we can introduce by the diet, Panax ginseng extract is one of the most utilized since it contains a vast number of bioactive molecules such as phenolic acids, flavonoids, and polysaccharides that have been shown to possess antioxidant, anti-ageing, anti-cancer, and immunomodulatory activity. In this work, the ability of a P. ginseng extract in combination with a probiotic formulation was taken into consideration to evaluate its effects on the modulation of in vitro reconstructed human gut microbiota (HGM). After evaluating the growth of the individual strains on the ginseng extract, we tested the in vitro reconstructed HGM setup (probiotics, minimal core, and whole community) using 2% w/v ginseng as the only carbon and energy source. The probiotic strains reached the highest growth, while the minimal core and the whole community showed almost the same growth. Specifically, the presence of the ginseng extract favors L. plantarum and B. animalis subsp. lactis among the probiotics, while B. cellulosilyticus prevails over the other strains in the minimal core condition. In the presence of both probiotics and minimal core strains, L. plantarum, B. animalis subsp. lactis, and B. cellulosilyticus reach the highest growth values. The bacterial metabolites produced during ginseng extract fermentation in the three conditions were administered to human intestinal epithelial cells (HT-29) to investigate a potential antioxidant effect. Remarkably, our results highlighted a significant reduction in the total ROS and a slightly reduction in the cytosolic superoxide anion content in HT-29 cells treated with bacterial metabolites deriving from ginseng extract fermentation by the whole community.